Control Scheme for a DC Grid Manager in a Tiny House - Koning, Sebastiaan; Zuidervliet, Diego; Van Duijsen, Peter (2025 19th Conference on Electrical Machines, Drives and Power Systems (ELMA), 2025)
The proliferation of DC nano-grids in rural communities has heightened the demand for electrical engineers proficient in power electronics and DC grid systems. For students studying these subjects, both theoretical and practical knowledge is essential, particularly in implementing a grid manager within a DC grid. This paper proposes a control scheme for a grid manager in a DC nano-grid, designed as a practical assignment for students. The control scheme is independent of converter topology and processor type, allowing simultaneous control of multiple outputs with various configurations. PI controllers and a droop control algorithm are utilized to manage power flow. An online dashboard visualizes the power flow within the grid manager, enabling configuration of the control algorithm to meet grid requirements. This control scheme has been tested in an experimental environment to validate its effectiveness in managing a DC nano-grid.